Analysis of QoS in the user's perspective of the Common Services in Cellular Systems UMTS/3G and LTE (A Case Study of mobile Networks in Angola). - Luemba, Barros Helder S. (Midlands State University, 2017)
The purpose of this research is to determine the main factors affecting Quality of Service based on mobile Third Generation (3G) and Fourth Generation (4G) service in Angola. The main reason to stimulate the present study was the significantly low rate speed on 3G and 4G service among mobile users in Angola where unlike many other countries the rate of this usage runs in opposite way. Thanks to increasing advances in wireless communications devices, the number of mobile users has growingly increased and as a result the development of mobile commerce (e-commerce) has been accelerated. The research attempts to examine the factors predicting consumer intention for 3G and 4G adoption in Angola. For the purpose of the research, the diffusion of innovation model and some other variables are integrated including awareness, affordability, accessibility and acceptability. The research findings revealed that in view of consumers, acceptability, accessibility, affordability seem more significant than awareness in regard with 4G adoption. Identifying the above factors will drive telecommunication operators in Angola to provide more successful 4G services to enhance the rate of 4G service adoption.